If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 265 + -6x = 39x + 15 Reorder the terms: 265 + -6x = 15 + 39x Solving 265 + -6x = 15 + 39x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-39x' to each side of the equation. 265 + -6x + -39x = 15 + 39x + -39x Combine like terms: -6x + -39x = -45x 265 + -45x = 15 + 39x + -39x Combine like terms: 39x + -39x = 0 265 + -45x = 15 + 0 265 + -45x = 15 Add '-265' to each side of the equation. 265 + -265 + -45x = 15 + -265 Combine like terms: 265 + -265 = 0 0 + -45x = 15 + -265 -45x = 15 + -265 Combine like terms: 15 + -265 = -250 -45x = -250 Divide each side by '-45'. x = 5.555555556 Simplifying x = 5.555555556
| x^3+7x^2+200=0 | | 6(x-5)=-30 | | 15x=3(x-1)-4(1-x) | | -3=3(x+6) | | 149-5x=22x+23 | | 5x+13=-137-10x | | 7-5(x-2)=5-3(x+3) | | 11-9x=29-16x | | -9+2z=9z+12 | | 2(x-1)-3(2-x)+4(1-x)=0 | | -23-4x=9-8x | | -134-7x=8x+16 | | -5(k+5)+5k= | | 5(b-4)+25= | | 0=3(2-3x)-7(x-3) | | 10+2(4y+3)= | | 3x-2(12-x)=4(2x-3)+3(x+1) | | 6-5c=-14 | | 6(1-x)+4=3(2-x)-4 | | 4x+10=90-6 | | 40-2(x+1)=90 | | 4k+6=6k-2 | | 6(2x+1)+7=9x+1 | | 6x+9=-119-10x | | 3(7x-1)+8(3-2x)=1 | | -2*5= | | 5(2x+3)-3(x+1)=5 | | 8(x-2)-2(2x-1)=2x+1 | | -2(5r+3)= | | 5a+30b=25 | | 5(3x-4)=8x+1 | | 6a-4=8 |